2022
DOI: 10.1039/d1cp05748k
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron circular dichroism in angle-resolved photoemission from liquid fenchone

Abstract: We present an experimental X-ray photoelectron circular dichroism (PECD) study of liquid fenchone at the C 1s edge. A novel setup to enable PECD measurements on a liquid microjet [Malerz...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 72 publications
0
14
0
Order By: Relevance
“…Note that such a methodology may have a broad range of interests since it could be applied to any type of chirality, beyond the asymmetric-carbon central chirality case [31], as well as beyond the gas phase since PECD has been recently demonstrated in liquid fenchone [32].…”
Section: Discussionmentioning
confidence: 99%
“…Note that such a methodology may have a broad range of interests since it could be applied to any type of chirality, beyond the asymmetric-carbon central chirality case [31], as well as beyond the gas phase since PECD has been recently demonstrated in liquid fenchone [32].…”
Section: Discussionmentioning
confidence: 99%
“…PECD was predicted by Ritchie, 42 Cherepkov 143 and Powis 43 and first detected by Bo ¨wering et al 45 It has now been extended to the multiphoton [58][59][60] and strong-field ionization regimes, 71,144 to liquid targets, 145 is being adopted for industrial applications 146 and proposed as a key mechanism in a photophysical astrophysical scenario for the origin of life's homochirality. 12 In PECD, the circularly polarized field…”
Section: Photoelectron Circular Dichroism (Pecd)mentioning
confidence: 96%
“…29 Aqueous-phase PECD is a yet untouched field of research, with literally no results reported from aqueous solution but a single pioneering study on liquid fenchone has been reported. 120 Detection and quantification of PECD in aqueous environment would indeed be a major accomplishment for several reasons. It potentially enables the characterization of the effect of hydrogen-bonding and of the interaction with solvation-shell ions on PECD, by way of comparison with measurements for a suitable reference molecule performed in the gas phase.…”
Section: Near-threshold Ionization Processes In Liquid Water and Aque...mentioning
confidence: 99%